Seasonal hydrological and suspended sediment transport dynamics in proglacial streams, James Ross Island, Antarctica. Issue 1 (2nd January 2017) - Kavan, Jan; Ondruch, Jakub; Nývlt, Daniel; Hrbáček, Filip; Carrivick, Jonathan L.; Láska, Kamil
ABSTRACT: Rapid warming of the Antarctic Peninsula is producing accelerated glacier mass loss and can be expected to have significant impacts on meltwater runoff regimes and proglacial fluvial activity. This study presents analysis of the hydrology and suspended sediment dynamics of two proglacial streams on James Ross Island, Antarctic Peninsula. Mean water discharge during 8 January 2015 to 18 February 2015 reached 0.19 m 3 s −1 and 0.06 m 3 s −1 for Bohemian Stream and Algal Stream, respectively, equivalent to specific runoff of 76 and 60 mm month −1 . The daily discharge regime strongly correlated with air and ground temperatures. The effect of global radiation on proglacial water discharge was found low to negligible. Suspended sediment concentrations of Bohemian Stream were very high (up to 2927 mg L −1 ) due to aeolian supply and due to the high erodibility of local rocks. Total sediment yield (186 t km −2 yr −1 ) was high for (nearly) deglaciated catchments, but relatively low in comparison with streams draining more glaciated alpine and arctic catchments. The sediment provenance was mostly local Cretaceous marine and aeolian sediments; volcanic rocks are not an important source for suspended load. High Rb/Sr ratios for some samples suggested chemical weathering. Overall, this monitoring of proglacial hydrological and suspended sediment dynamics contributes to the dearth of such data from Antarctic environments and offers an insight to the nature of the proglacial fluvial activity, which is likely to be in a transient state with ongoing climate change.